Characterization of CO2 Laser Photoacoustic Spectrometer Intracavity Configuration and Its Application in Measuring Acetone Gas in Human Breath: CO2 Laser Photoacoustic Spectrometer Intracavity Configuration and Acetone Gas Concentration - Mitrayana; Muyasaroh, Nurul; Wasono, Mohammad Ali Joko; Ikhsan, Mohammad Robikhul (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Photoacoustic spectrometer is a very effective instrument for detecting low concentration gasses. In this research, a CO2 laser photoacoustic spectrometer intracavity configuration was characterized and applied for measuring acetone gas concentration in human exhaled breath during exercise on a treadmill. The characterization included laser power optimation, scanning laser spectrum, making resonant curve and quality factor, measuring noise and background signal, determining lowest detection and linearity curve. Acetone gas concentration was determined by analyzing normalized photoacoustic signal using multicomponent matrix. The optimum power was obtained at 32.4 ± 0.5 W and CO2 laser spectrum consisted of four line groups. The highest laser absorption line of standard acetone gas was determined at 10P20. Quality factor was obtained at 14.6 ± 0.6, noise at 1.7 ± 0.2 μV/Hz1/2, background signal at 10P20 0.001 to 0.004 mV, lowest detection limit of acetone gas at 110 ± 14 ppbV, and acetone gas linearity gradient on 10P20 was at ????????22 = 0.0140 ± 0.0007. Acetone gas concentration in human exhaled breath after exercising on treadmill decreased from 43 % to 79 % than before.